Immunomodulatory perspectives of potential biological spices with special reference to cancer and diabetes. Issue 4 (4th July 2017) - Imran, Muhammad; Nadeem, Muhammad; Saeed, Farhan; Imran, Ali; Khan, Moazzam Rafiq; Khan, Muhammad Asif; Ahmed, Sheraz; Rauf, Abdur
ABSTRACT: In millennia, nutritionists are motivated to explore innovative approaches against lifestyle-related syndromes for improving public health and life span. Spices are the promising and cost-effective choice for consumer owing to their high antioxidant potential, that is, ability to entrap free radicals at cellular level to alleviate various metabolic syndromes. Besides that, spices are not only popular in developed countries, but also attaining consideration in developing world due to extensive biological activity and safe status. In this regard, contemporary nutrition regime has gained researchers' attention on spices to mitigate various metabolic syndromes. Moreover, the promising bioactive moieties – that is, curcumin and curcuminoids (turmeric); limonene (cardamom), allicin, allyl isothiocyanate (garlic), cinnamic aldehyde, 2-hydroxycinnamaldehyde, and eugenol (cinnamon); gingerol, zingiberone, zingiberene (ginger), dipropyle disulfides, and quercetin (onion); piperidine piperine, limonene, α - and β -pinene (black pepper); crocetin, crocin, and safranal (saffron) – have been identified as chemopreventing agents against various malignancies.